The case for macroscale through-thickness reinforcement for hybridised multifunctional composites - Neale, Geoffrey; De La Cruz Martinez, Marisa L.; Skordos, Alexandros A. (Cranfield University, 2024)
Embedding fundamental functional properties like thermal and electrical conductivity in composites is key in deriving a range of additional industrially-useful functionalities. Through-thickness reinforcement (TTR) can achieve this via material hybridisation. These techniques are sometimes unattractive due to the need for specialised equipment and a shortage of available expertise to support TTR. A knowledge gap exists in understanding the interplay between reinforcement size and functional behaviour especially where reinforcements go beyond traditional geometrical constraints. Here we demonstrate that the addition of macroscale (≥1 mm) TTR can significantly improve electro-thermal energy transfer as well as provide effective tailoring functionality in composites.